Rancang Bangun Sistem Informasi Umat Gereja Katolik Gembala Yang Baik Surabaya Berbasis Web - Romadlan, Safwat Sulung; Sunarto, M. J. Dewiyani; Soebijono, Tony (Jurnal JSIKA, 2013)
Abstract: Problems faced by Shepherd Church Which Is Whether ( GYB) Surabaya is not own the information report of about people data which accurate enough to council paroki as base to take the decision. To get the this people data, Church conduct the data or people census of exist in its region periodical. But unhappily, people data [of] result of this census oftentimes documentation do not better. As a result, change, seeking, and conducted difficult data processing. Pursuant to the problems is hence required by an information system of people base on the web owning function as medium to accomodate the people data and conduct the record-keeping which is usually conducted by pastoral like record-keeping sakramen, record-keeping of mutation of family and family member, record-keeping of death and record-keeping of member activity. Where each;every record-keeping can yield the report of concerning people required by pastoral council. Information system base on this web applicable to manage the people data, record-keeping of sakramen people, death record-keeping, and mutation record-keeping, able to present the people list as according to family card and yield the report of concerning card of family and people. With the existence of information system this web, information of concerning visible other record-keeping and people by pastoral council to be used as by the basis for decision making.   Keywords: Church Database, People Data, Web Based.